Religion, Nationalism, and Violence: An Integrated Approach - Gorski, Philip S. (Annual review of sociology, 2013)
Scholarly work on the nexus of religion, nationalism, and violence is currently fragmented along disciplinary and theoretical lines. In sociology, history, and anthropology, a macro-culturalist approach reigns; in political science, economics, and international relations, a micro-rationalist approach is dominant. Recent attempts at a synthesis ignore religion or fold it into ethnicity. A coherent synthesis capable of adequately accounting for religious-nationalist violence must not only integrate micro and macro, cultural and strategic approaches; it must also include a meso level of elite conflict and boundary maintenance and treat the religious field as potentially autonomous from the cultural field.